Anatomy Ontologis for Bioinformatis Princiles and practice
Bioinformatics as a discipline has come of age, and there are now numerous databases and tools that are widely used by researchers in the biomedical field. However, successful development of future bioinformatics applications will depend on an appropriately formalised representation of domain knowledge. This book provides a timely and first-of-its-kind collection of contributed chapters on anatomy ontologies. It is interdisciplinary in its approach, bringing together relevant expertise from computing and biomedical studies, and covering both theoretical and applied aspects, with an emphasis on newer work relevant to the emerging Semantic Web. This book provides a comprehensive discussion of the foundations of anatomical ontologies and the state-of-the-art in existing computational tools and applications. It considers a number of fundamental modelling principles. It includes chapters about research on algorithms to systematically align anatomy ontologies and to mine data in the literature, using anatomy terms. It explains recent efforts to develop a common anatomy reference ontology. It discusses anatomy in the context of spatio-temporal biomedical atlases. It describes systems and tools for linking anatomy ontologies with each other and with other on-line resources, such as the biomedical literature. It highlights the challenges of dealing with anatomy-based information on the Semantic Web. Although primarily written for readers who will be involved in developing the next generation of IT applications in the areas of life sciences, biomedical sciences and health care, this unique volume will be of interest to anyone who will further develop anatomy ontologies, who will use them, and who will be involved in the actual development of relevant (semantic) web applications.